2021
DOI: 10.3390/medicina57060562
|View full text |Cite
|
Sign up to set email alerts
|

Atrial and Ventricular Structural and Functional Alterations in Obese Children

Abstract: Background and objectives: Childhood obesity has reached epidemic levels in the world. Obesity in children is defined as a body mass index (BMI) equal to or above the 95th percentile for age and sex. The aim of this study was to determine early changes in cardiac structure and function in obese children by comparing them with their nonobese peers, using echocardiography methods. Materials and methods: The study enrolled 35 obese and 37 age-matched nonobese children. Standardized 2-dimensional (2D), pulsed wave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
(50 reference statements)
0
3
0
Order By: Relevance
“…Despite a large amount of literature reporting associations between childhood obesity, systemic hypertension, and diabetes with cardiac structure and function, there is a paucity of research investigating these associations in multi-ethnic cohorts of healthy children (35)(36)(37)(38)(39). Large United Kingdom studies such as those of Barker and the ALSPAC cohort predominately include those of WE origin (40,41).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite a large amount of literature reporting associations between childhood obesity, systemic hypertension, and diabetes with cardiac structure and function, there is a paucity of research investigating these associations in multi-ethnic cohorts of healthy children (35)(36)(37)(38)(39). Large United Kingdom studies such as those of Barker and the ALSPAC cohort predominately include those of WE origin (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in obese children have also reported that despite preserved systolic cardiac function, there is sub-clinical diastolic dysfunction. This is due to impaired myocardial relaxation as indicated by reduced mitral inflow velocities ( 38 , 39 , 46 ). There are also reports that children with increased CV risk due to underlying chronic conditions such as renal disease or diabetes have sub-clinical diastolic dysfunction which may be associated with other subtle changes in CV status ( 37 , 46 , 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in obese children have also reported that despite preserved systolic cardiac function, there is subclinical diastolic dysfunction. This is due to impaired myocardial relaxation as indicated by reduced mitral inflow velocities (38,39,46). There are also reports that children with increased CV risk due underlying chronic conditions such as renal disease or diabetes have sub-clinical diastolic dysfunction which may be associated with other subtle changes in CV status (37,46,47).…”
Section: Discussionmentioning
confidence: 99%